Sowing the seeds of massive black holes in small galaxies: young clusters as the building blocks of ultracompact dwarf galaxies - Amaro-Seoane, Pau; Konstantinidis, Symeon; Freitag, Marc Dewi; Miller, M. Coleman; Rasio, Frederic A. (The astrophysical journal, 2014)
Interacting galaxies often have complexes of hundreds of young stellar clusters of individual masses ∼104-106 M ☉ in regions that are a few hundred parsecs across. These cluster complexes interact dynamically, and their coalescence is a candidate for the origin of some ultracompact dwarf galaxies. Individual clusters with short relaxation times are candidates for the production of intermediate-mass black holes of a few hundred solar masses, via runaway stellar collisions prior to the first supernovae in a cluster. It is therefore possible that a cluster complex hosts multiple intermediate-mass black holes that may be ejected from their individual clusters due to mergers or binary processes, but bound to the complex as a whole. Here we explore the dynamical interaction between initially free-flying massive black holes and clusters in an evolving cluster complex. We find that, after hitting some clusters, it is plausible that the massive black hole will be captured in an ultracompact dwarf forming near the center of the complex. In the process, the hole typically triggers electromagnetic flares via stellar disruptions, and is also likely to be a prominent source of gravitational radiation for the advanced ground-based detectors LIGO and VIRGO. We also discuss other implications of this scenario, notably that the central black hole could be considerably larger than expected in other formation scenarios for ultracompact dwarfs.